P448 Long term effectiveness of first-line infliximab treatment compared to conventional treatment in paediatric moderate-to-severe Crohn's disease – an update from the TISKids study. (30th January 2023) - Vuijk, S; Jongsma, M; Cozijnsen, M; van Pieterson, M; de Meij, T; Norbruis, O; Groeneweg, M; Wolters, V; van Wering, H; Hojsak, I; Kolho, K L; Hummel, T; et al.
Abstract: Background: Current guidelines recommend first-line anti-TNF therapy (start at diagnosis) only in children with high risk for a complicated disease course. However, previous results of the TISKids study showed that first-line infliximab (FL-IFX) treatment (5 infusions in total) combined with azathioprine (AZA) was more effective to achieve clinical remission without treatment escalation at week 52 compared to conventional induction treatment (CONV) with AZA in therapy-naïve children with moderate-to-severe CD, irrespective of having high risk for development of complications 1 . The aim of our study was to investigate the effects at 3-year follow-up of the TISKids cohort. Methods: The TISKids study is a multicentre, open-label randomised controlled trial in which untreated patients with a new diagnosis of CD (3–17 years old, weighted paediatric CD activity index score >40) were included. Patients were randomised to FL-IFX (5 infusions of 5 mg/kg infliximab at weeks 0, 2, 6, 14, 22) or CONV (EEN or prednisolone). Both treatment groups were combined with AZA maintenance. The primary outcome was biochemical remission (faecal calprotectin <250 ug/g) without need for additional biological treatment at 3 years. Secondary outcomes were time to additional biological treatment and number of patients with luminal surgery until 3 years. Additional biological treatment in the FL-IFX group included intensification, continuation or restart of IFX. Differences in proportions were tested using the Chi-square or Fisher-exact test, time to additional biological was analysed using Kaplan-Meier method with log-rank test. Results: In total, 50 patients received FL-IFX and 47 CONV. One patient from each group was lost to follow-up, data at 3 years was available in 89/97 patients. At 3 years, 5/43 (12%) FL-IFX patients were in biochemical remission without need for additional biological treatment compared to 4/42 (10%) CONV patients (p=1.00). The time to additional biological treatment was significantly longer for the FL-IFX patients (median 63 weeks) compared to CONV patients (median 32 weeks), p=0.019. The number of luminal surgeries (all ileocaecal resections) until 3 years was not significantly different between FL-IFX (n=2/46, 4%) compared to CONV (n=5/43, 12%), p=0.256. Conclusion: These results imply that there still is a significant benefit of FL-IFX during 3 years of follow-up (longer time to additional biological treatment compared to CONV), demonstrating durability of providing effective induction treatment. Further research should identify in which patient and when IFX may be stopped and which maintenance treatment would be appropriate in order to sustain and further optimize the benefits of FL-IFX treatment. 1. Jongsma MME et al. Gut. 2020. PMID: 33384335